Role of miRNA-495 and NRXN-1 and CNTN-1 mRNA Expression and Its Prognostic Importance in Breast Cancer Patients. (8th October 2021) - Alkhathami, Ali G.; Verma, Amit Kumar; Alfaifi, Mohammed; Kumar, Lalit; Alshahrani, Mohammad Yahya; Hakami, Abdulrahim R.; Alshehri, Osama M.; Asiri, Mohammed; Ali Beg, Mirza Masroor
Abstract : Breast cancer is a heterogeneous disease in which genetic factors are involved in disease worsening and higher mortality. Epidemiological and clinical research revealed that breast cancer incidence continues to rise. 100 histopathologically confirmed untreated newly diagnosed cases of invasive ductal carcinoma (IDC) of breast and 100 healthy subjects were involved and blood samples were collected in non-EDTA plain vials. Serum was separated by centrifugation, total RNA was extracted from serum, and cDNA synthesis was done to study the miRNA-495 and neurexin-1 (NRXN-1) and contactin 1 (CNTN-1) mRNA expression by QRT-PCR. The expression levels of miRNA-495, NRXN-1, and CNTN-1 were expressed in fold change. The present study observed decreased relative miRNA-495 expression (0.07-fold) while an increase in NRXN-1 (11.61-fold) and CNTN-1 (4.92-fold) was observed among breast cancer patients compared to healthy controls. A significant difference was observed in miRNA-495 expression with menopausal status (p = 0.0001 ) and TNM stages (p = 0.02 ). It was observed that NRXN-1 expression was significantly associated with menopausal status (p = 0.03 ), lymph node involvement (p < 0.0001 ), estrogen receptor (ER) status (p = 0.03 ), progesterone receptor (PR) status (p = 0.005 ), TNM stages (p < 0.0001 ), and distant metastases (p < 0.0001 ). CNTN-1 expression was also found to be associated with lymph node involvement (p = 0.01 ), PR status (p = 0.03 ), HER2 status (p = 0.04 ), TNM stages (p < 0.0001 ), and distant metastases (p < 0.0001 ). ROC suggested that NRXN-1 and CNTN-1 could be the important predictive marker for disease advancement and distant organ metastases. The study concluded that the decreased expression of miR-495 observed in breast cancer patients showed a negative correlation with NRXN-1 while the increased expression of NRXN-1 and CNTN-1 was linked with disease advancement and distant metastases and could be the important predictive marker for breast cancer patients.